DEVELOPMENT OF METHODICAL METHODS FOR ASSESSING AGRICULTURAL LAND PLOTS USING A RISK-BASED APPROACH BASED ON GEOINFORMATION SYSTEMS - Elena Vasilievna Bondar; Andrey Vladimirovich Skripchinskiy; Roman Yurievich Sedykh (Наука. Инновации. Технологии)
Introduction: A risk-based approach can significantly reduce the total number of inspections, their planning, ranking by the degree of risk. Materials and methods of research: when developing methodological methods for assessing land plots, the criteria for classifying the activities of economic entities were taken into account. To identify land plots, the publicly available remote sensing data of the Earth was used. The generated database contains the coordinates of the cetroids of the land parcels and the risk category. Based on the created cartographic materials, an analysis of the effectiveness of the application of the risk-based approach for the assessment of agricultural land is made. Results and discussion: Based on the proposed methodology for applying the risk-based approach, the land plots located in the Ipatovsky, Arzgirsky, Blagodnenskoye, Trunovsky, Aleksandrovsky, Izobilnensky, Georgievsky, Kursk districts, as well as most of the Grachevsky and Andropov districts, will be checked only on applications from citizens and in the event of a threat to the life and health of people. Mapping of land subject to checks with the data of administrative violations of the land legislation in the period from 2015 to 2017 has identified municipal areas, where the rates of offences had values above medium-range, but the planned inspection of land will not be carried out, namely in the following areas: Ipatovskiy, Blagodarnenskiy and Novoseletskiy. Spatial analysis of the location of land areas subject to inspections in municipal areas with the maximum share of offenses identified only four land plots in the Turkmen district, the lack of audited sites in the western part of the Kochubeevskiy district, the northwestern part of the Novoaleksandrovskiy district, the southern part of the Predgorniy district, and the western and southern parts of the Krasnogvardeyskiy district. spatial analysis showed weak effectiveness of the risk-based approach without taking into account regional characteristics, possible threats to sustainable development of land use and protection of agricultural land in the Stavropol region.